2005
DOI: 10.1523/jneurosci.4230-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates for Behaviorally Conditioned Immunosuppression in the Rat

Abstract: We have previously demonstrated behaviorally conditioned immunosuppression using cyclosporin A as an unconditioned stimulus and saccharin as a conditioned stimulus. In the current study, we examined the central processing of this phenomenon generating excitotoxic lesions before and after acquisition to discriminate between learning and memory processes. Three different brain areas were analyzed: insular cortex (IC), amygdala (Am), and ventromedial nucleus of the hypothalamus (VMH). The results demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 73 publications
5
66
0
2
Order By: Relevance
“…Conversely, the amygdala has been found to mediate the afferent signals at the time of acquisition. The ventromedial hypothalamic nucleus has been found to participate in the efferent signals to the immune system, which are necessary to elicit the behaviorally conditioned immune response (252,253).…”
Section: Many Immune Responses Can Be Placebo Conditionedmentioning
confidence: 99%
“…Conversely, the amygdala has been found to mediate the afferent signals at the time of acquisition. The ventromedial hypothalamic nucleus has been found to participate in the efferent signals to the immune system, which are necessary to elicit the behaviorally conditioned immune response (252,253).…”
Section: Many Immune Responses Can Be Placebo Conditionedmentioning
confidence: 99%
“…We employed a wireless recording method, allowing unrestricted animal behaviour, minimizing stress artefacts and providing in our hands reliable electrophysiological data [41]. The study focused on the Am and IC since these structures have previously been shown to be involved in immune-visceral inputs, independently of the afferent route involved [36,[42][43][44], and because lesion experiments documented the relevance of these two structures during processing immune signals employed as unconditioned stimuli [45][46][47]. Furthermore, in independent experiments, changes in body temperature and circulating cytokine profiles were monitored to further evaluate the immune reactivity under the various experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, both in multiple sclerosis patients [55] and in healthy subjects [56], immunosuppression after placebo could be induced after conditioning with immunosuppressive drugs, possibly by calcineurin inhibition [57]. In an attempt to elucidate the nervous structures involved in central processing of conditioned immunosuppression, Pacheco-López et al [58] carried out selective excitotoxic lesions of rat brain, highlighting a role for the amygdala and the insular cortex in the acquisition phase, and for the insular cortex and the ventromedial nucleus of the hypothalamus in the evocation phase. All these data should be interpreted in the light of psychoneuroimmunological research, where recent findings have identified neural circuits that operate reflexively, with an afferent branch bringing to the central nervous system (CNS) information about injury and infection, and an efferent branch operating through cholinergic and catecholaminergic output in the autonomic nervous system, the most prominent example being perhaps the cholinergic anti-inflammatory pathway.…”
Section: Placebo Responses Can Employ Brain -Body Pathwaysmentioning
confidence: 99%